1994
DOI: 10.1097/00000658-199412000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss and Dietary Intake After Vertical Banded Gastroplasty and Roux-en-Y Gastric Bypass

Abstract: ObjectiveThe purpose of this study was to learn whether preoperative eating habits can be used to predict outcome after vertical banded gastroplasty (VBG) and Roux-en-Y gastric bypass (RYGB).Background Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
191
2
25

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 317 publications
(232 citation statements)
references
References 16 publications
14
191
2
25
Order By: Relevance
“…The presence of a rapid and a slow phase of weight reduction following gastric bypass has been well documented [26]: this profile is due mainly to the pattern of energy intake, which is extremely low in the early postoperative period and, then, progressively increases up to 1 year after surgery [13,26,27]. Our results clearly indicate that, besides energy intake, other factors can influence weight loss at different phases of the process.…”
Section: Discussionsupporting
confidence: 63%
“…The presence of a rapid and a slow phase of weight reduction following gastric bypass has been well documented [26]: this profile is due mainly to the pattern of energy intake, which is extremely low in the early postoperative period and, then, progressively increases up to 1 year after surgery [13,26,27]. Our results clearly indicate that, besides energy intake, other factors can influence weight loss at different phases of the process.…”
Section: Discussionsupporting
confidence: 63%
“…One of the RCTs that they did include used a horizontal, unbanded gastroplasty 85 and therefore should have been excluded. Four other RCTs comparing vertical banded gastroplasty with gastric bypass [86][87][88][89] as well as three retrospective series [90][91][92] and the SOS cohort trial 17 all found gastric bypass to cause greater weight loss than gastroplasty. One study not cited by either report found an equivalent weight loss between vertical banded gastroplasty and gastric bypass when patients were allowed to choose the operation, but the drop-out rate (15% seen at 5 y) was excessive.…”
Section: Resultsmentioning
confidence: 99%
“…A significant increase in energy intake over time has been reported among bariatric surgery patients. 42,43 In the SOS study, self-reported intake was almost halved during the first 6 months postsurgically, from about 2900 to 1500 kcal per day, but increased to about 2000 kcal per day over the next 6 years. 14 These data suggest that surgical patients have difficulties to adhere to the postoperative diet.…”
Section: Discussionmentioning
confidence: 99%